Nezhat's operative gynecologic laparoscopy and hysteroscopy - Nezhat, Camran; Nezhat, Farr R.; Nezhat, Ceana (Cambridge University Press, 2008)
Gynecologic laparoscopy has evolved into a major surgical tool used to treat a multitude of gynecologic indications. Laparoscopy is the most common surgical procedure performed by gynecologists today. This book catalogs the full spectrum of laparoscopic procedures in gynecology, oncology, and infertility treatment. The authors describe different techniques in minimally invasive surgery and review the evidence-based medical literature supporting these techniques. Included are sections on the management of complications during laparoscopy, ranging from vascular injury to bladder or bowel injury. It contains expanded chapters on laparoscopic anatomy, operative hysteroscopy and pelvic floor repair. The editors have pioneered some of the most important laparoscopic procedures used today. Their work has opened up the video laparoscopy field for surgeons worldwide. The contributors have extensive experience in laparoscopy and hysteroscopy, and many of them have established some of the surgical techniques discussed. High-quality color pictures supplement many of the presentations.